Respuesta :

Answer:

[tex](11)\ -2x + 5y = 20[/tex]

[tex](12)[/tex]   [tex]4x + y= -25[/tex]

[tex](13)[/tex]   [tex]3x + 8y = -15[/tex]

[tex](14)\ -9x + 4y = 2[/tex]

[tex](15)\ y = - 9[/tex]

Step-by-step explanation:

Required

The line equation

[tex](11)\ (-5,2); m =\frac{2}{5}[/tex]

The equation is calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = \frac{2}{5}(x - (-5)) + 2[/tex]

[tex]y = \frac{2}{5}(x +5) + 2[/tex]

Open bracket

[tex]y = \frac{2}{5}x +2 + 2[/tex]

[tex]y = \frac{2}{5}x +4[/tex]

Multiply through by 5

[tex]5y = 2x + 20[/tex]

Rewrite as:

[tex]-2x + 5y = 20[/tex]

[tex](12)\ (-6, -1);\ m = -4[/tex]

The equation is calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = -4(x - -6) - 1[/tex]

[tex]y = -4(x +6) - 1[/tex]

Open bracket

[tex]y = -4x -24 - 1[/tex]

[tex]y = -4x -25[/tex]

Rewrite as:

[tex]4x + y= -25[/tex]

[tex](13)\ (3,-3)\ m =-\frac{3}{8}[/tex]

The equation is calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = -\frac{3}{8}(x - 3) -3[/tex]

[tex]y = -\frac{3}{8}x + \frac{9}{8} -3[/tex]

Multiply through by 8

[tex]8y = -3x + 9 - 24[/tex]

[tex]8y = -3x -15[/tex]

Rewrite as:

[tex]3x + 8y = -15[/tex]

[tex](14)\ (0, \frac{1}{2}); m = \frac{9}{4}[/tex]

The equation is calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = \frac{9}{4}(x - 0) + \frac{1}{2}[/tex]

[tex]y = \frac{9}{4}x + \frac{1}{2}[/tex]

Multiply through by 4

[tex]4y = 9x + 2[/tex]

Rewrite as:

[tex]-9x + 4y = 2[/tex]

[tex](15)\ (\frac{16}{3}, -9); m =0[/tex]

The equation is calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = 0(x - \frac{16}{3}) - 9[/tex]

[tex]y = 0 - 9[/tex]

[tex]y = - 9[/tex]

ACCESS MORE